Methods for On-Farm Testing of Peanut Varieties in Florida with Results from 2005–2009 - Barry L. Tillman; Mark W. Gomillion; Justin McKinney; George Person; Bill D. Thomas; Clyde Smith (EDIS)
SS-AGR-331, a 5-page illustrated fact sheet by B.L. Tillman, M.W. Gomillion, J. McKinney, G. Person, W.D. Thomas, and C. Smith, presents ideas for comparing the performance of varieties on a “farm scale” that will give peanut growers tools to accurately evaluate peanut varieties on their own farm. Published by the UF Department of Agronomy, March 2010.